THE INFORMATION SOCIETY AND ITS POLICY AGENDA: TOWARDS A HUMAN RIGHTS-BASED APPROACH - Pekari, Catrin (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2005)
This article reviews the existing broad variety of theories on the Information Society, including market or labour force-based approaches, stressing the expansion of the information sector and the increasing importance of knowledge work, technically deterministic concepts based upon the ideas of the information revolution and the computerization of society, and more comprehensive theories embracing those issues and aligning them with socio-political aspects. Against this backdrop, policy implications are evaluated, focusing on the results reached during the First Phase of the World Summit on the Information Society (WSIS). Although its relatively broad policy agenda, which favours an integrated approach for the coordination of Information Society issues, including areas such as health, development, education or the media, is, as such, a positive development, a coherent framework is still missing. The current paradigm remains rather technically deterministic, thus emphasizing the mainstreaming of information and communication technologies (ICTs), instead of calling attention to the underlying needs and rights that should be fostered and enhanced. It is argued that building an inclusive Information Society requires a paradigmatic shift towards a human rights-based approach.